Egeria densa Planchón (Hydrocharitaceae) : A new angiospermic record for Bangladesh - Alfasane, Md. Almujaddade; Khondker, Moniruzzaman; Islam, Md. Shafiqul; Bhuiyan, M. Azmal Hossain (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Egeria densa; Hydrocharitaceae; New record; Bangladesh. DOI: 10.3329/bjpt.v17i2.6702 Bangladesh J. Plant Taxon. 17(2): 209-213, 2010 (December)